Cohort study of occupational risk factors of low back pain in construction workers. Issue 1 (1st January 2000) - Latza, Ute; Karmaus, Wilfried; Stürmer, Til; Steiner, Markus; Neth, Axel; Rehder, Uwe
Abstract : OBJECTIVES: To identify work related risk factors of future low back pain (LBP) in a cohort of construction workers free of LBP at the start of follow up. METHODS: The Hamburg construction worker study comprises 571 male construction workers who have undergone two comprehensive interview and physical examination surveys. A cohort of 285 subjects without LBP at baseline was identified. After a follow up of 3 years, the 1 year prevalence of self reported LBP was determined in the 230 men followed up (80.7%). Prevalence ratios (PRs) with 95% confidence intervals (95% CIs) of LBP at follow up according to self reported work tasks of construction workers measured at baseline were estimated from Cox's regression models which were adjusted for age, and anthropometric measures. RESULTS: At follow up 71 out of 230 workers (30.9%) reported LBP during the preceding 12 months. Four work tasks (scaffolding, erecting roof structures, sawing wood, laying large sandstones) with an increased risk of 1 year prevalence of LBP at follow up were further evaluated. After further adjustment for occupation the relative risk was increased for workers who had reported ⩾2 hour/shifts laying large sandstones (PR=2.6; 95% CI 1.1 to 6.5). Work load of bricklayers was additionally estimated by an index on stone load (high exposure: PR=4.0; 95% CI 0.8 to 19.8), and an index for laying huge bricks/blocks (yes/no: PR=1.7; 95% CI 0.5 to 5.7). CONCLUSIONS: The results suggest that self reported differences in brick characteristics (size and type of stone) and temporal aspects of the work of bricklayers (average hours per shift laying specified stones) can predict the future prevalence of LBP. The data have to be interpreted with caution because multiple risk factors were tested.